Reduced L-Selectin Expression with Increased Anti-Apoptotic Protein in the Lymphocytes of Rheumatoid Arthritis Patients - Haider Faisal Ghazi; Asmaa Baqir Al-Obaidi; Hind Shaker Al-Mammori (Diyala Journal of Medicine, 2019)
Background: Rheumatoid arthritis is a chronic inflammatory disease of the synovium with uncertain pathogenesis. A number of phenotypic and functional T-cell defects have been described in rheumatoid arthritis.